The power of our names, faces, and the self-reference effect: is there more than meets the eye? - Desebrock, C (Psychology Postgraduate Affairs Group, 2019)
In mythological tales, our names and facial images are often gifted a quasi-magical power. When psychologists use these self-representations (or even items we simply imagine are ‘me/mine’) as stimuli in experimental tasks, studies have shown that our perception, memory, decision-making, and actions can be enhanced. The phenomenon has been termed the Self-Reference Effect (SRE). Does an underlying ‘self’ mechanism underpin these effects? Or, do the effects arise because the stimuli are simply more rewarding, familiar, or deeply-encoded? Could the empirical treatment of the SRE be echoing a faulty folk-intuition that the self is a unitary entity? This article briefly explores the colourful history of self-representations, the research field of the SRE, and some of its key challenges.